'Doing the right thing': How social science can help foster pro-environmental behaviour change in marine protected areas. (July 2017) - Martin, Victoria Y.; Weiler, Betty; Reis, Arianne; Dimmock, Kay; Scherrer, Pascal
Abstract: Managers of marine protected areas (MPAs) are constantly challenged to encourage positive user behaviour to minimise impacts on marine ecosystems while allowing recreational use. Yet, some marine users continue to act in ways that diminish conservation values of the area. Drawing on social psychological theories, this paper presents a case for informed behaviour change strategies to reduce problem behaviours in MPAs and contribute to conservation efforts. Social psychological drivers of behaviour are explained and applied to an MPA context to demonstrate how they can inform strategies for predicting and changing behaviour using persuasive communication. As behavioural and persuasive communication theories are seldom invoked and almost never rigorously applied to MPAs, the review offers new theoretical and practical insights into how they can assist MPA management to target and shift specific behaviours that ultimately support marine park values. Highlights: Presents decision flowchart to guide theory-driven MPA user behaviour change. Identifies constructs and theories of relevance to changing marine user behaviour. Reviews persuasive communication theory and research in environmental contexts. Examples of applications of behaviour change research in marine environments. A model of factors influencing MPA user behaviour and behaviour change.